2022
DOI: 10.3390/ijerph19148680
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Approaches in Family Health Promotion as an Opportunity for Health Behavior Change—A Rapid Review

Abstract: Background: With their influence on health behavior of children, families are important addressees in health promotion and prevention of chronic diseases. However, they are often difficult to reach, partly due to the open approach of health promotion services. Therefore, they should be addressed directly and be involved in shaping their living environment. The aim is to examine which approaches are used in participatory family health promotion and what practical experiences are made. Methods: A systematic lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(148 reference statements)
0
1
0
2
Order By: Relevance
“…Outro elo dos itens da Family Health Scale foi observado entre os fatores II (estilo de vida saudável da família) e IV. O ambiente familiar tem um impacto significativo no desenvolvimento do comportamento alimentar e na prática de atividade física em crianças 30 , na prevenção de condições crônicas em saúde não transmissíveis nos diferentes ciclos de vida e na promoção de hábitos e estilos de vida saudáveis 31 . Todavia, comportamentos não saudáveis são identificados em famílias mais pobres 32 .…”
Section: Discussionunclassified
“…Outro elo dos itens da Family Health Scale foi observado entre os fatores II (estilo de vida saudável da família) e IV. O ambiente familiar tem um impacto significativo no desenvolvimento do comportamento alimentar e na prática de atividade física em crianças 30 , na prevenção de condições crônicas em saúde não transmissíveis nos diferentes ciclos de vida e na promoção de hábitos e estilos de vida saudáveis 31 . Todavia, comportamentos não saudáveis são identificados em famílias mais pobres 32 .…”
Section: Discussionunclassified
“…The family unit plays an unparalleled role in maintaining health, preventing disease and sustainable care, because members may support and nurture one another through various life stages (Barnes et al., 2020). Many previous studies have shown that a healthy family promotes closeness and a sense of belonging among family members (Huang et al., 2021; Rejaän et al., 2021), provides mutual care (Fisher et al., 2020), guides healthy behaviours (Kuchler et al., 2022) and protects members from external risks (Prime et al., 2020). Therefore, it is important to understand whether and how family health could be associated with HRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…Mit Hilfe dieses theoretischen Arsenals hat sich ein Forschungsfeld konstituiert, das in eine Vielzahl von in sich schlüssigen Projekten mündet [6,23,34,72]. Es sind aber über die Jahre auch einige Problemlagen entstanden, die sich fast zwangsläufig aus der Genese dieses Felds und seines Instrumentariums zu ergeben scheinen.…”
Section: Introductionunclassified